Is yoga cultural appropriation? - Danielle Thompson-Ochoa (Wolters Kluwer Medknow Publications, 2019)
Introduction: Yoga was originally founded in South Asia and it was practiced by various South Asian individuals. It is a spiritual practice about the mind and body, as well as the meaning of life and the nature of the universe. The intended belief was yoga assist with self-development believed to reduce stress, increase beauty, strength, and muscle flexibility. Aim and Objective: The main objective of this article is to highlight how yoga has transformed into controversial, elite, counter cultural and pop culture varieties with undertones of cultural appropriation. Argument: The case of yoga and its appropriation by the Western culture creates a paradoxical situation. In this situation, approval and adoption of yoga in the West has made the practice more trendy and popular among middle-class urban Indian consumers and helped re-brand the practice. Such re-marketing has allowed to make yoga more appealing to the modern consumer and more concerned with the aspects related to physical performance, health and scientific explanation. Conclusion: Although the notion of cultural appropriation can be discussed in the negative light, the article explores how yoga has transformed from a sacred practice to cultural appropriation by Western culture.